Changing the record: reassessing effectiveness and value in prison music projects - Doxat-Pratt, Sarah (2019)
This thesis proposes a new approach for understanding and articulating the value of prison music projects. It responds to a report from the Arts Alliance (now National Criminal Justice Arts Alliance), which stated that ‘arts organisations had still not managed to unpick what the arts does and how it does it’ in a prison context (Arts Alliance, Evidence Library (2011), 35). This suggests that much attention has been focused on the ‘effects’ of musical interventions, but not enough on the critical attendant questions: how, why, and for whom? Funding demands and political and cultural developments have meant that the pressure to prove results and satisfy legislators is felt by researchers, practitioners and participants.